2020
DOI: 10.1101/2020.01.10.901363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term exposure to high-water temperature causes a shift in the microbiome of the common aquarium spongeLendenfeldia chondrodes

Abstract: Marine sponges harbor diverse microbiomes that contribute to their energetic and metabolic needs. Although numerous studies on sponge microbial diversity exist, relatively few focused on sponge microbial community changes under different sources of environmental stress. In this study, we assess the impact of elevated seawater temperature on the microbiome of cultured Lendenfeldia chondrodes , a coral reef sponge commonly found in marine aquaria. Lendenfeldia chondrodes exhibits high thermal tolerance showing n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…2). In contrast, the abundance of other OTUs in L. chondrodes ’ core microbiome ( sensu Vargas et al 2021) barely differed between foliose and thread-like sponges, with only an acidobacterium (OTU_3) and a proteobacterium (OTU_5) increasing their abundance (LFC = 1.95 and 0.69, respectively; t 17.08 = 3.18, Bonferroni corrected p-value = 0.049 and t 29.81 = 3.82, Bonferroni corrected p-value = 0.006, Fig. 3 and Suppl.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…2). In contrast, the abundance of other OTUs in L. chondrodes ’ core microbiome ( sensu Vargas et al 2021) barely differed between foliose and thread-like sponges, with only an acidobacterium (OTU_3) and a proteobacterium (OTU_5) increasing their abundance (LFC = 1.95 and 0.69, respectively; t 17.08 = 3.18, Bonferroni corrected p-value = 0.049 and t 29.81 = 3.82, Bonferroni corrected p-value = 0.006, Fig. 3 and Suppl.…”
Section: Resultsmentioning
confidence: 97%
“…control condition) on the composition of the sponge microbiome. In addition, for the nine most abundant core OTUs (Vargas, Leiva, & Wörheide, 2021) we tested for significant changes in OUT frequency in control vs . shaded sponges using Hotelling’s T-Square test.…”
Section: Methods and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected Actinobacteria because specific primers previously tested in sponges are readily available, and we expected this taxon to be insensitive to the shading treatment in contrast to the photosynthetic Cyanobacterium. Besides, OTUs belonging to these bacterial phyla occur in L. chondrodes (Vargas, Leiva, & Wörheide, 2021). For this, we extracted DNA from three control and three bleached L. chondrodes explants using the NucleoSpin® Tissue kit (Macherey-Nagel).…”
Section: Qpcr-based Abundance Estimation Of Cyanobacteria and Actinob...mentioning
confidence: 99%
“…There are, however, fewer studies characterizing holobiont‐associated microbial dynamics in response to elevated temperatures. To date, studies have shown that temperature influences microbial composition in corals (Wang et al, 2018; Ziegler et al, 2017), sponges (Erwin et al, 2012; Vargas et al, 2020), oysters (Lokmer & Wegner, 2015), anemones (Mortzfeld et al, 2016), and mussels (Li et al, 2019), among others (Brothers et al, 2018). These studies typically focus on a single time‐point across a geographic range or temporal variability at a single site (Li et al, 2018; Ward et al, 2017; Woo et al, 2017); rarely are these approaches combined.…”
Section: Introductionmentioning
confidence: 99%